Электродвигатели с катящимся ротором - Борзяк Юрий Гордеевич (Технiка, 1982)
Экземпляры: КХ (20121025) / Инвентарный номер: 788081 / Цена: 0.45 / Сис.шифр: 621.34 / Авт.знак: Б 82 / ГРНТИ: 44.31 / ББК: 31